The new sociology of health is addressing global diseases and novel paradigms - Sifuentes León, Eudosio (2021)
The increasing prevalence of global diseases, some of which are among the top ten leading causes of death, emerges as an attribute of this era, appearing in reports from the World Health Organization, PAHO, UNDP, the World Bank, and Ministries of Health in several countries. The world health situation was different when Sociology was forming its classical thinking (1820-1920), with a predominance of infectious and epidemic diseases in regional settings, which received obligatory attention from physicians and biologists. As we enter the 21st century, infectious and epidemic diseases coexist with the growth of chronic and degenerative diseases, now requiring an intervention where experts in Epidemiology and Public Health associated with the social sciences predominate. This time sociology has a theoretical-practical framework that includes collective health as part of its program, facing two realities: the impacts of global epidemic diseases and the development-application of new paradigms in science.